Energy Performance of Cool Roofs Followed by Development of Practical Design Tool - Saber, Hamed H.; Maref, Wahid (Frontiers in Energy Research, 2019)
Cool/white roofing systems use paints and membranes with high solar reflectivity to reflect a portion of the incident solar radiation resulting in lowering the temperature of the exterior surfaces in respect of the conventional/black roofing systems. This study focuses on the energy performance of roofing system that is being used in buildings of the Gulf Cooperation Council countries when this roof is exposed to a hot and humid climatic conditions in Saudi Arabia. The long-term moisture performance of the white and black roofing systems were investigated in a previous study in which the results showed that no risk of condensation and mould growth occurred in the roofs with different values of solar reflectivity of the rooftop and different initial construction moisture. With the same environmental conditions that were used in the previous study, the focus of this paper is on assessing the energy performance of white and black roofing systems for a wide range of: (a) thermal insulation thickness, and (b) solar reflectivity of the rooftop. Also, considerations are given in this study to develop a practical design tool that can easily be used by building engineers and architects for determining all pairs of the insulation thickness and the corresponding solar reflectivity of the reflective roofing materials/coatings that resulted in the same levels of the energy performance as those for the black roofing systems of thicker insulation thickness. The results of this study along with the developed practical design tool can be used in future to upgrade the Saudi building code to allow using less insulation in the roofs if white roofing systems are installed.